Multifunctional Microtubule-Associated Proteins in Plants - Krtková, Jana; Benáková, Martina; Schwarzerová, Kateřina (Frontiers in Plant Science, 2016)
Microtubules (MTs) are involved in key processes in plant cells, including cell division, growth and development. MT-interacting proteins modulate MT dynamics and organization, mediating functional and structural interaction of MTs with other cell structures. In addition to conventional microtubule-associated proteins (MAPs) in plants, there are many other MT-binding proteins whose primary function is not related to the regulation of MTs. This review focuses on enzymes, chaperones, or proteins primarily involved in other processes that also bind to MTs. The MT-binding activity of these multifunctional MAPs is often performed only under specific environmental or physiological conditions, or they bind to MTs only as components of a larger MT-binding protein complex. The involvement of multifunctional MAPs in these interactions may underlie physiological and morphogenetic events, e.g. under specific environmental or developmental conditions. Uncovering MT-binding activity of these proteins, although challenging, may contribute to understanding of the novel functions of the MT cytoskeleton in plant biological processes.